ANALISIS KEPENTINGAN INDONESIA DALAM MERATIFIKASI PIAGAM ASEAN (ASEAN CHARTER) - Muh Kadarisman (Faculty of Social and Political Sciences Universitas Kristen Indonesia, 2014)
Abstracts: The research question is what is Indonesia’s interest in ratifying ASEAN Charter? Theresearch purpose is to understand and analyse factors that become beackground of the Indonesiangovernment to ratify ASEAN Charter. Method: analytical descriptive, making description in systematic,factual and acurate way on facts, characteristics and relation among phenomenon that have beenresearched to get complete information about the important of Indonesian government in ratifiyingASEAN Charter. Technique of data collection is by library research. Data is analysed qualitatively byconnecting factors and phenomenon related to the research, to have result and answer which compatiblewith the research purpose. The result of research are firstly the interest of Indonesia to ratify ASEANCharter is closely connected with the development of relations among nations in the world, which need tomake adjustments toward its foreign policies to guarantee Indonesia national interest based on stronglegality. Secondly, the area cooperation in the initial formation of ASEAN is still functional which are inthe field of economics, social, knowledge and technology. The present development of internationalpolitics is increasing the awareness of members of ASEAN countries to conduct collective cooperation toencourage the process of regional integration either in economics, politics or sociocultural and toreduce all obstacles in creating regional integration and stability so that ASEAN cooperation becomesmore solid.Key Words: National Interest, ASEAN Integration Abstrak: Permasalahan penelitian: Apa kepentingan Indonesia dalam meratifikasi Piagam ASEAN?Tujuan penelitian: Untuk memahami dan menganalisis hal-hal yang melatarbelakangi PemerintahIndonesia meratifikasi Piagam ASEAN. Metode penelitian: menggunakan deskriptif analitis, yaitumembuat suatu gambaran secara sistematis, faktual, dan akurat mengenai fakta-fakta, sifat-sifat sertahubungan antar fenomena yang diteliti, sehingga mendapatkan informasi menyeluruh tentang pentingnyapemerintah Indonesia meratifikasi Piagam ASEAN. Teknik pengumpulan data, dengan studi kepustakaan.Analisis data, menggunakan analisis kualitatif yaitu menghubungkan faktor-faktor dan gejala-gejalayang terkait dengan penelitian, sehingga didapatkan hasil atau jawaban sesuai dengan tujuan penelitian.Hasil penelitian ini adalah pertama, kepentingan Indonesia dalam meratifikasi Piagam ASEAN, eratkaitannya dengan semakin berkembangnya hubungan antar bangsa-bangsa di dunia, yang membutuhkanpenyesuaian-penyesuaian terhadap kebijakan politik luar negeri demi terjaminnya kepentingan nasionalIndonesia atas dasar hukum yang kuat (legal personality). Kedua,lingkup kerja sama awal terbentuknyaASEAN adalah masih bersifat fungsional, yaitu di bidang ekonomi, sosial, ilmu pengetahuan danteknologi. Perkembangan politik internasional kini menumbuhkan kesadaran negara Anggota ASEANguna melakukan kerja sama kolektif dalam mendorong proses integrasi regional lebih luas baik di bidangekonomi, politik maupun sosial budaya, serta menghilangkan segala hambatan guna terciptanyaintegrasi dan stabilitas regional, sehingga menjadikan kerja sama ASEAN semakin solid.Kata Kunci: Kepentingan Nasional, Integrasi ASEAN